Quality during milling of a glass fiber reinforced polymer composite - Uysal, Alper; Altan, Mihrigul (CARL HANSER VERLAG, 2015)
Glass fiber reinforced polymer composites are used as different structural components and machining processes are generally performed to fixing and assembling operations. Milling is one of them used in reaching the final dimensions and shapes of these composites. In this study, glass fiber reinforced polymer composite plates were milled under different cutting parameters such as depth of cut, feed and cutting speed. High speed steel and tungsten carbide cutting tools were used in the experiments. Relation between cutting parameters with surface roughness were investigated in details. Design of experiment was also used to determine the optimal cutting condition for minimum surface roughness. Analysis of variance was applied to determine the effectiveness of the parameters. Finally, cutting performance of the fibers along the edges of the milled surfaces was investigated according to selection of the tool and milling conditions.
Keywords: Milling; glass fiber reinforced polymer composite; surface roughness; Taguchi method; analysis of variance; SURFACE-ROUGHNESS; PLASTICS; TAGUCHI; PARAMETERS; PRECISION; DRILL; Materials Science